Prompt penetration effects on Equatorial Electrojet from the Indian sector - R. K. Archana; Kusumita Arora; Nandini Nagarajan (Earth, Planets and Space, 2023)
Abstract The morphology of prompt penetration effects (PP) in the Equatorial Electrojet (EEJ) at Vencode (VEN, Geomagnetic latitude 0.29ºN) was studied using 5-min samples of EEJ and interplanetary Ey component data from 2011 to 2015. In contrast to previous studies that mainly focused on storm-time PP events, our study investigated the characteristics of PP effects on EEJ during both quiet and disturbed periods. Our findings reaffirm earlier reports of high PP efficiency during local noon for both quiet and disturbed days. Moreover, PP amplitudes were greater when IMF-Bz was oriented northward compared to southward, indicating the presence of overshielding effects even during quiet conditions. Additionally, we examined seasonal variations in PP amplitudes and observed weaker PP during the solstice compared to the equinox. Furthermore, our study analysed the equatorial counter electrojet (CEJ) caused by PP events associated with northward-turning IMF-Bz. We report 15% of CEJs at VEN associated with PP effects; a few PP events were observed while the equatorial electric field at VEN was already westward (i.e. PP within CEJ), indicating the combined effects of magnetospheric and ionospheric perturbations. Identifying CEJs caused by PP during quiet days helps to differentiate between magnetospheric and ionospheric mechanisms/processes. Additionally, we investigated the spatial variability in PP amplitudes at closely spaced sites, utilizing one year of concurrent data from Minicoy (MNC, Geomagnetic latitude 0.19ºN), VEN, and Campbell Bay (CBY, Geomagnetic latitude 0.29ºN) situated at geographic longitudes 72º, 77º and 93º, respectively. Our results showed significant differences in PP amplitudes between VEN-CBY and MNC-CBY, separated by 15º and 20º longitude, respectively. Observations from the three equatorial sites demonstrated a longitudinal trend, with PP amplitudes increasing westward towards MNC, inverse to the amplitudes of EEJ. Graphical Abstract